No-Code Digital Learning Innovation for Islamic Education: Development and Usability Evaluation of a GlideApps-Based Instructional Media - Hamdani Hamdani; Abdul Rahman; Haidah Haidah; Andi Syarifuddin; Prapdopo Prapdopo; Satryawati Satryawati; Heldina Pristanti (CV. Science Tech Group, 2025)
The transformation of digital learning in vocational education requires media innovations that adapt to the characteristics of digital-native students. This research aims to develop and evaluate GlideApps-based Islamic Religious Education learning media as an effective, adaptive, and accessible no-code solution. Using the ADDIE model, this research involves the stages of needs analysis, multimodal content design, application development, implementation on a limited and broad scale, and usability evaluation. Data was obtained through observations, interviews, and questionnaires from a total of 96 students. The study's results show that students need flexible, visual, and interactive media to better understand Islamic Education materials. The design process yielded an app with intuitive navigation, structured modules, interactive quizzes, and multimedia support. Expert validation shows a very high level of feasibility in both the material (89%) and media design (87%) aspects. User implementation shows that the app is easy to use and supports both self-paced and structured learning. The usability evaluation recorded an average score of 4.41 (88.13%), indicating excellent effectiveness, efficiency, and user satisfaction. The indicators of ease of understanding the material and ease of use obtained the highest score (4.53). These results confirm that GlideApps meets the principles of multimodal learning and technology acceptance theory. This study concludes that GlideApps media is efficacious in improving accessibility, engagement, and student learning experience, while offering a no-code media development model that can be replicated in the context of religious and humanities learning in vocational education environments.